Upaya Perbaikan Pemenuhan Kebutuhan Packing Box di PT. Schneider Electric Manufacturing Batam (SEMB) - Steven Purnama Wijaya; Felecia Felecia (Jurnal Titra, 2023)
In the industrial world, suppliers or suppliers of raw materials are very important to meet production needs. Supplier delays in sending raw materials can be a serious problem in the industrial world. This is what happened to PT. Schneider Electric Manufacturing Batam (SEMB) in recent times. Suppliers of packing box raw materials often do not deliver according to the requests ordered every day resulting in a shortage on the production floor. The research method used in this research is Define, Measure, Analyze, Improve, and Control (DMAIC). From the research results, it was found that there was an error on the part of the supplier in reading the forecast, demand that was considered sudden from the supplier, there was no notification when a part was not sent, and the difficulty of communicating with the supplier. Based on the results of this study, solutions were made to solve these problems including pre-alerts, build stock alerts, and stock visibility. This improvement has been proven to have reduced the number of shortages from samples taken on part W917271080111P which previously occurred 8 times in 1 month to none.